The World and the Cave: Imagination, Public Space and Politics with Hannah Arendt and José Saramago - Teerds, Hans (Writingplace, 2020)
Imagination, Hannah Arendt argues, is the human capacity to mentally remove oneself and see things from a different perspectives. It allows to imagine how things can be different. As such, this capacity is as much the source of political action as well as of architectural design. Architectural imagination - as well as understanding - might flourish when fed by perspectives from other professional fields, like philosophy, social sciences, theology, as well as other artistic fields, like literature, painting, and sculpture. In this paper, Hans Teerds proposes an exemplary reading beyond the borders of the architectural profession by means of a comparative reading of Hannah Arendt’s 1958 The Human Condition and the novel The Cave (2000) by the Portuguese writer Jose Saramago. By reading them together, this paper explore perspectives upon public space, mass consumption and production, and craftsmanship, which, highlight political aspects of architecture.